No founder effect in three novel Alzheimer's disease families with APP 717 Val-->Ile mutation. Clerget-darpoux. French Alzheimer's Disease Study Group. Issue 8 (August 1996) - Campion, D; Brice, A; Hannequin, D; Charbonnier, F; Dubois, B; Martin, C; Michon, A; Penet, C; Bellis, M; Calenda, A; Martinez, M; Agid, Y; et al.
Abstract : We sequenced exons 16 and 17 of the APP (amyloid precursor protein) gene in 18 unrelated French Alzheimer's disease (AD) patients. These patients had an onset before the age of 60 and belonged to families with autosomal dominant transmission of the disease. We detected the APP 717 Val-->Ile mutation in three out of 18 (16.6%) families. In these three families, all affected subjects had the APOE 3/3 genotype, but their ages of onset ranged from 38 to 60 years, indicating that factors other than the APOE genotype influence age of onset. Analysis of two polymorphic loci adjacent to the APP gene showed that at least two independent mutational events had occurred within these pedigrees, in spite of their origin in the same region of France.